Towards a New Theory of Citizenship: Migration Rights in the Chilean Case; [Hacia Una Nueva Teoría de la Ciudadanía: Derechos de la Migración en el Caso Chileno] - Rivera-Cubillos, D (HISIN (History of Information Systems), 2024)
Introduction: This article investigates how migration processes impact human rights and redefine the conception of citizenship, using a qualitative case study based on the Chilean experience. Methodology: It applies a qualitative, descriptive and explanatory approach, analysing from a historical-theoretical perspective the contributions of classical sociologists on citizenship rights and how these have been influenced by migration. Analysis and Results: The analysis demonstrates that the traditional notion of citizenship, centred on residence, national identity and legal guarantees, is insufficient in the current context. The findings suggest that modern citizenship must transcend simple national membership and political participation, encompassing a broader spectrum of social and human dimensions. Conclusions: The study concludes that citizenship should not be viewed in a reductionist or exclusively legal manner, but as a multidimensional concept that needs to be rethought to reflect the realities of global migration and cultural interconnectedness. It highlights the need for a more inclusive and adaptive approach to citizenship in the contemporary world. © 2024, HISIN (History of Information Systems). All rights reserved.